2013
DOI: 10.4236/jsemat.2013.31001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chemical Composition and Thermal Sprayed Method on the Chromium and Tungsten Carbides Coatings Microstructure

Abstract: The microstructure, phase consistence and microhardness of thermal sprayed coatings were investigated. The tungsten and chromium carbide coatings and also composite NiCrSiB coating were analyzed. The microstructure of coatings were observed by using optical microscopy (MO), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Almost equiaxial carbide particles settled inside the surrounded material of coating were found. The cracks propagating thorough the particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…In addition the thickness of the coatings had measured between the 893.36 and 340.64 µm, which is in accordance with many studies in the literature [12,24,25]. The measured surface roughness was 0.1-0.3 µm and porosity of the coating had ranged between 1 and 4%, which is in the acceptable range.…”
Section: Microstructural Characterizationsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition the thickness of the coatings had measured between the 893.36 and 340.64 µm, which is in accordance with many studies in the literature [12,24,25]. The measured surface roughness was 0.1-0.3 µm and porosity of the coating had ranged between 1 and 4%, which is in the acceptable range.…”
Section: Microstructural Characterizationsupporting
confidence: 74%
“…In order to overcome this problem, and to reduce the cost per foot, surface modification techniques such as chemical vapor deposition (CVD), boron ion implantation [6][7][8][9], pulse-plasma deposition [10], laser surface modification [11], thermal spray techniques (TS) [12], etc., have been studied for protecting the drill bits against wear, fluid erosion and corrosion [6][7][8]. Some of these coating techniques, CVD, boron ion implantation and pulse-plasma deposition, are reported as not suitable for rock drilling applications due to thin thickness of the protective layer and its inferior bonding strength with the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The authors revealed that their 200-μm thick coating, which was prepared with gun movement velocity of 1000 mm/s and spray distance of 200 mm, had the lowest porosity (approximately 1 per cent) and the highest corrosion-wear resistance in H 2 SO 4 0.5M (Suegama et al , 2004). In addition, the structure and properties of Cr 3 C 2 -NiCr coating fabricated by HVOF technique have been also reported in the literature (Richert et al , 2013; Zavareh et al , 2015; Guilemany et al , 2002; Magnani et al , 2009; Ji et al , 2007; Matikainen et al , 2017).…”
Section: Introductionmentioning
confidence: 80%
“…Cermet coating materials specially WC-Co and CrC-NiCr systems are usually applied in services involving high erosion and corrosion conditions, however, WC-Co is the most successful metallurgical product due to its superior properties compared to the CrC-NiCr system [2,3]. Richert et al [4] compared several W and Cr carbides as well as composite NiCrSiB coatings where they reported that the hardness of the W coatings was higher than those of the chromium ones. Furthermore, results showed that WC-Co-Cr is harder than WC-Co coating due to the presence of Cr 7 C 3 , Cr 23 C 6 carbides formed through the decarburization of carbides [4].…”
Section: Introductionmentioning
confidence: 99%
“…Richert et al [4] compared several W and Cr carbides as well as composite NiCrSiB coatings where they reported that the hardness of the W coatings was higher than those of the chromium ones. Furthermore, results showed that WC-Co-Cr is harder than WC-Co coating due to the presence of Cr 7 C 3 , Cr 23 C 6 carbides formed through the decarburization of carbides [4]. Schwetzke and Kreye [5] characterized WC-12Co and WC-10Co-4Cr coatings with different types of HVOF where they reported that the former coating type is softer and less wear-resistant than the latter one.…”
Section: Introductionmentioning
confidence: 99%